Enhancing E-Learning Engagement and Effectiveness: A Post-Pandemic Evaluation of German Language Students’ Perceptions and Outcomes - Ahooie, Zeinab; Panjehshahi, Parastoo; Fazelzad, Armin (Assessment and Practice in Educational Sciences, 2026)
The COVID-19 pandemic precipitated a rapid global shift to online education, challenging traditional pedagogical practices, particularly in language learning, which relies heavily on communicative interaction. This study investigates post-pandemic experiences of 180 undergraduate German language students in Tehran who had participated in both pre-pandemic in-person and post-pandemic online learning. Using a structured Likert-scale questionnaire, the study assessed student satisfaction, engagement, communication, and perceived learning outcomes across three domains: student experience, learning outcomes, and communication quality. Results indicate high levels of satisfaction with instructor communication and learning flexibility, with 91% of students rating instructor interactions positively and 57.8% expressing a preference for online or hybrid formats. While peer interaction in digital environments was less robust, strong correlations emerged between communication satisfaction and learner motivation, underscoring the importance of well-structured digital interaction tools. The findings highlight the benefits of post-pandemic online education, including schedule autonomy, content accessibility, and self-paced learning, while identifying persistent challenges in fostering spontaneous peer engagement. The study situates its analysis within the Community of Inquiry framework, emphasizing the interdependence of teaching, social, and cognitive presence in creating meaningful online learning experiences. By providing empirical evidence on student perceptions in a hybrid post-pandemic context, the research contributes to ongoing discussions about effective e-learning design, learner autonomy, and culturally sensitive pedagogical strategies. The study concludes that hybrid models, when paired with high-quality communication channels and digital infrastructure, can sustain student motivation and engagement, offering practical insights for instructors, instructional designers, and policymakers seeking to develop resilient, learner-centered language education programs. Future research should expand on these findings using longitudinal designs, diverse institutional settings, and performance-based assessments of language proficiency to further optimize online and hybrid learning strategies.